Avaliação de técnicas de banho de aspersão carrapaticida em bovinos de produção de leite - Daniel Sobreira Rodrigues (2012)
Failures in applying acaricide are considered as a constraint for the success of control of Rhipicephalus (Boophilus) microplus. Nevertheless, there are few studies on the subject. The aim of this work was to evaluate different methods of spraying dairy cattle. For this purpose were used 106 cows at the reproductive age and observations conducted for 24 months. The Power Spray was the only method to get positive assessments both in the categories: physical ergonomics; presence of blockages and leaks, and the complete surface skin wetting. The mean and standard deviation values for time required on procedure and consumption of acaricide fluid for each animal were: 01min12s ± 38s and 4.29 ± 1.48 L for the Usual method; 04min8s ± 35 s and 3.68 ± 0.33 L for hand pumped Backpack Sprayer; 06s ± 05s and 3.78 ± 0.60 L, for Spray Race; 01min35s ± 13s and 3.37 ± 0.84 L for Power Spray. The calculated costs per application were US$ 0.43, US$ 0.61, US$ 0.32, US$ 0.46, respectively. The Power Spray treatment killed 58% of the ticks and was more efficient in reducing tick burden (p<0,001) than Usual method and Spray Race, that killed 45% and 48%, respectively. There was no significantly difference between the Backpack Sprayer and the others. Among the techniques evaluated the power spray showed the greatest advantages and therefore should be prioritized.